2014
DOI: 10.1016/j.phrp.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Molecular and Conventional Diagnostic Tests for Detecting Tuberculosis in Korea, 2013

Abstract: ObjectivesA fast and accurate diagnosis is necessary to control and eliminate tuberculosis (TB). In Korea, TB continues to be a serious public health problem. In this study, diagnostic tests on clinical samples from patients suspected to have TB were performed and the sensitivity and specificity of the various techniques were compared. The main objective of the study was to compare various diagnostic tests and evaluate their sensitivity and specificity for detecting tuberculosis.MethodsFrom January 2013 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…Many studies used real-time PCR for detection of mutations in rpoB and katG genes 17 , 18 , 19 , 20 , 21 but, to our knowledge, this study is the first one that uses the TaqMan allelic discrimination without MGB. Our study suggests that drug-resistant M. tuberculosis can be detected by pattern's curve or Ct with TaqMan probes without MGB in real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies used real-time PCR for detection of mutations in rpoB and katG genes 17 , 18 , 19 , 20 , 21 but, to our knowledge, this study is the first one that uses the TaqMan allelic discrimination without MGB. Our study suggests that drug-resistant M. tuberculosis can be detected by pattern's curve or Ct with TaqMan probes without MGB in real-time PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al . [ 10 ] in a large-scale study reported the sensitivity and specificity of smear microscopy as 56.8% and 99.6%, respectively, while that of real-time PCR for solid culture was reported as 97.2% and 72.4%, respectively, and for liquid culture was 93.5% and 97.2%, respectively. Congruent results have been reported recently by Agarwal et al .…”
Section: Answersmentioning
confidence: 99%
“…Outro grande problema na sua implantação é o custo elevado da tecnologia em comparação com baciloscopia e a necessidade de calibração anual, que é susceptível de ser difícil em ambientes remotos. 12,15,17 No entanto, a Foundation for Innovative New Diagnostics (FIND) negociou reduções substanciais nos custos para uso no setor público em 116 países de alta carga de tuberculose e de baixa e média renda. O custo de capital inicial para o instrumento GeneXpert nesses ambientes (cerca de US$ 17.500 por instrumento de 4 módulos) é consideravelmente maior do que para microscopia (cerca de US $ 1.500 por diodo emissor de luz [LED] microscópio), mas muito menor do que para a cultura convencional, especialmente tendo em vista que se pode dispensar a necessidade de caros equipamentos de biossegurança.…”
Section: 12-16unclassified
“…Estudo realizado na Coreia 22 relatou sensibilidade e especificidade da baciloscopia de 56,8% e 99,6%, respectivamente. Enquanto, a sensibilidade e especificidade do Xpert ® MTB/RIF para a cultura sólida foram 97,2% e 72,4%, respectivamente, enquanto que os dados correspondentes para a cultura líquida foi de 93,5% e 97,2%.…”
Section: Estudounclassified